Development of a novel urban-rural relationship for sustainable nitrogen cycle: Casestudy in Hai Phong City - Nguyễn, Thu Hoài (2020)
The remainder of master thesis is structured into six chapters as described below: Chapter one highlights the literature review, where the origin of nitrogen in ecosystem, the definition of waste sludge and the sludge recovery systems were introduced. Chapter two highlights the general information of Hai Phong city and the methodology of the research that explains detail the data collection and analyzing process. Chapter three highlights the potential of recovery and reuse nitrogen to produce waste-based fertilizer. Chapter four: The assessment of citizens and farmers in waste-based fertilizer were surveyed and the situation of emptying septage sludge and agriculture activities were determined. Chapter five: Three Sustainable and integrated waste-based nitrogen management scenarios were examined, as well as the baseline scenario, to verify the potential of recovery and reuse nitrogen from waste sludge. The series guideline of resource recovery and reuse (RRR) in developing countries which is reported by the International Water Management Institute were the assessment tools for three scenarios. Chapter six gives the conclusions and recommendations.